Major Depressive Disorder Alters Perception of Emotional Body Movements - Kaletsch, Morten; Pilgramm, Sebastian; Bischoff, Matthias; Kindermann, Stefan; Sauerbier, Isabell; Stark, Rudolph; Lis, Stefanie; Gallhofer, Bernd; Sammer, Gebhard; Zentgraf, Karen; Munzert, Joern; Lorey, Britta (Frontiers in Psychiatry, 2014)
Much recent research has shown an association between mood disorders and an altered emotion perception. However, these studies were conducted mainly with stimuli such as faces. This is the first study to examine possible differences in how people with major depressive disorder (MDD) and healthy controls perceive emotions expressed via body movements. 30 patients with MDD and 30 healthy controls observed video scenes of human interactions conveyed by point–light displays (PLDs). They rated the depicted emotions and judged their confidence in their rating. Results showed that patients with MDD rated the depicted interactions more negatively than healthy controls. They also rated interactions with negative emotionality as being more intense and were more confident in their ratings. It is concluded that patients with MDD exhibit an altered emotion perception compared to healthy controls when rating emotions expressed via body movements depicted in PLDs.